Response of Oil Palm Seedling (Elaeis guineensis) In Pre Nursery On Giving Doses of Nasa Liquid Organic Fertilizers and Intervals - Yetti Elidar (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2019)
Response of  Oil Palm Seedling (Elaeis guineensis) In Pre Nursery On Giving Doses of Nasa Liquid Organic Fertilizers  and Intervals. The purpose of this research is to know the doses and interval of Nasa organic liquid fertilizer (OLF) and the combination of dosage and OLF Nasa interval to the best palm seeds in pre nursery. The research was conducted in UPTD Seed Plantation Plantation Supervision of East Kalimantan Province in 2015. The study used Factorial completely randomized design (CRD)  5 x 4 with nine replications. The first factor was the treatment of OLF Nasa doses in a concentration of 3 cc OLF Nasa per liter of water (D) consisting of 5 levels, namely: d0 = 0 ml OLF Nasa, d1 = 300 ml OLF Nasa, d2 = 400 ml OLF Nasa, d3 = 500 ml OLF Nasa and d4 = 600 ml OLF Nasa. The second factor is the treatment of OLF Nasa (I) Interval Interval consisting of 4 levels, namely: i1 = 1 week, i2 = 2 weeks, i3 = 3 weeks and i4 = 4 weeks. Thus there were 16 treatments and each treatment was repeated 9 times so that the total was 180 seeds. Data were analyzed statistically and tested further with the smallest real difference test (BNT) at 5% level.The results showed that the dosage of 500 ml OLF in the concentration of 3 cc OLF Nasa liter-1 of water gave the highest plant height that is an average 28.73 cm. While the OLF Nasa interval once a week gives the highest plant height is an average of 29.33 cm.